Agricultural Development and Environmental Research: American and Czechoslovak Perspectives: Proceedings of a Bilateral Workshop (The National Academies Press, 1987)
Keywords: Agriculture

Scientific Advances in Animal Nutrition: Promise for the New Century: Proceedings of a Symposium - National Research Council (The National Academies Press, 2001)
The science of animal nutrition has made significant advances in the past century. In looking back at the discoveries of the 20th century, we can appreciate the tremendous impact that animal nutrition has had on our lives. From the discovery of vitamins and the sweeping shift in the use of oilseeds to replace animal products as dietary protein sources for animals during the war times of the 1900s-to our integral understanding of nutrients as regulators of gene expression today-animal nutrition has been the cornerstone for scientific advances in many areas. At the milestone of their 70th year of service to the nation, the National Research Council's (NRC) Committee on Animal Nutrition (CAN) sought to gain a better understanding of the magnitude of recent discoveries and directions in animal nutrition for the new century we are embarking upon. With financial support from the NRC, the committee was able to organize and host a symposium that featured scientists from many backgrounds who were asked to share their ideas about the potential of animal nutrition to address current problems and future challenges.
Keywords: Agriculture

Professional Societies and Ecologically Based Pest Management: Proceedings of a Workshop - National Research Council (The National Academies Press, 2000)
The National Research Council's (NRC) Board on Agriculture and Natural Resources invited professional societies associated with agriculture and ecology to participate in a two-day workshop to explore leadership and a common vision for ecologically based pest management (EBPM). These proceedings describe the challenges of and opportunities for EBPM discussed by participants in the workshop.
Keywords: Agriculture

Mitigating the Nutritional Impacts of the Global Food Price Crisis: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
In 2007 and 2008, the world witnessed a dramatic increase in food prices. The global financial crisis that began in 2008 compounded the burden of high food prices, exacerbating the problems of hunger and malnutrition in developing countries. The tandem food price and economic crises struck amidst the massive, chronic problem of hunger and undernutrition in developing countries. National governments and international actors have taken a variety of steps to mitigate the negative effects of increased food prices on particular groups. The recent abrupt increase in food prices, in tandem with the current global economic crisis, threatens progress already made in these areas, and could inhibit future efforts.
Keywords: Food and Nutrition; Agriculture

Ecological Monitoring of Genetically Modified Crops: A Workshop Summary - National Research Council (The National Academies Press, 2001)
Proponents of agricultural biotechnology believe that genetically modified (GM) crops have the potential to provide great ecological benefits, such as reduced pesticide and land use, as well as agricultural benefits. However, given the rapid emergence of commercial GM crops and the likely increase in their use, many groups have raised concerns about the potential unintended, adverse ecological effects of these crops. Some ecological concerns are enhanced development of pest resistance, crosspollination with wild relatives, and reductions in beneficial insects or birds. Ecological Monitoring of Genetically Modified Crops considers the latest in monitoring methods and technologies and to asks--What are the challenges associated with monitoring for ecological effects of GM crops? Is ongoing ecological monitoring of GM crops a useful and informative activity? If so, how should scientifically rigorous monitoring be carried out in the variety of ecological settings in which GM crops are grown?
Keywords: Agriculture; Biology and Life Sciences

Using Models to Estimate Hog and Pig Inventories: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In 2014, the National Agricultural Statistics Service (NASS) engaged the National Academies of Sciences, Engineering, and Medicine to convene a planning committee to organize a public workshop for an expert open discussion of their then-current livestock models. The models had worked well for some time. Unfortunately beginning in 2013, an epidemic that killed baby pigs broke out in the United States. The epidemic was not fully realized until 2014 and spread to many states. The result was a decline in hog inventories and pork production that was not predicted by the models. NASS delayed the workshop until 2019 while it worked to develop models that could help in times both of equilibrium and shock (disease or disaster), as well as alternative approaches to help detect the onset of a shock. The May 15, 2019, workshop was consistent with NASS’s 2014 intention, but with a focus on a model that can help predict hog inventories over time, including during times of shock. This publication summarizes the presentations and discussions from the workshop.
Keywords: Agriculture; Surveys and Statistics

Soliciting Stakeholder Input for a Revision of Biosafety in Microbiological and Biomedical Laboratories (BMBL): Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since its publication by the National Institutes of Health (NIH) and the Centers for Disease Control and Prevention (CDC) in 1984, Biosafety in Microbiological and Biomedical Laboratories (BMBL) has become the cornerstone of the practice of biosafety in the United States and in many countries around the world. The BMBL has been revised periodically over the past three decades to refine the guidance it provides based on new knowledge and experiences—allowing it to remain a relevant, valuable, and authoritative reference for the microbiological and biomedical community. Seven years after the release of the BMBL 5th Edition, NIH and CDC are considering a revision based on the comments of a broader set of stakeholders. At the request of NIH, the National Academies of Sciences, Engineering and Medicine conducted a virtual town hall meeting from 4 April to 20 May 2016 to allow BMBL users to share their thoughts on the BMBL in general and its individual sections and appendices. Specifically, users were asked to indicate what information they think should be added, revised, or deleted. Major themes from the virtual town hall meeting were further discussed in a workshop held on 12 May 2016 in Washington, DC. This document encapsulates the discussion of the major comments on the BMBL that were posted on the virtual town hall prior to 12 May 2016 and the various BMBL comments and issues related to biosafety that were raised during the workshop by participants who attended the meeting in Washington DC and those who listened to the live webcast.
Keywords: Biology and Life Sciences; Agriculture

Managing Food Safety Practices from Farm to Table: Workshop Summary - Institute of Medicine (The National Academies Press, 2009)
Legal regulations and manufacturers' monitoring practices have not been enough to prevent contamination of the national food supply and protect consumers from serious harm. In addressing food safety risks, regulators could perhaps better ensure the quality and safety of food by monitoring food production not just at a single point in production but all along the way, from farm to table. Recognizing the troubled state of food safety, the Institute of Medicine's (IOM) Food Forum met in Washington, DC, on September 9, 2008, to explore the management of food safety practices from the beginning of the supply chain to the marketplace.
Keywords: Food and Nutrition; Agriculture

Animal Research in a Global Environment: Meeting the Challenges: Proceedings of the November 2008 International Workshop - National Research Council (The National Academies Press, 2011)
Animal research will play an essential role in efforts to meet increasing demands for global health care. Yet the animal research community faces the challenge of overcoming negative impressions that industry and academia engage in international collaborations in order to conduct work in parts of the world where animal welfare standards are less stringent. Thus, the importance of ensuring the international harmonization of the principles and standards of animal care and use cannot be overstated. A number of national and international groups are actively working toward this goal. The Institute for Laboratory Animal Research (ILAR), a program unit of the US National Research Council, is committed to promoting both the welfare of animals used in research and the quality of the resulting science. In 2008, to follow up on the 2003 event, ILAR convened a workshop which brought together 200 participants from 17 countries. Their mission was to identify and promote better understanding of important challenges in the conduct of animal research across country boundaries. These challenges include: the sourcing of animals; the quality of veterinary care; competent staff; the provision of a suitable environment (including nutritious food and potable water) for animals; and ongoing oversight of the animal program; among others. Animal Research in a Global Environment summarizes the proceedings of the 2008 workshop. The impact of this 2008 workshop has extended beyond the oral presentations conveyed in these proceedings. It has been a vital bridge for diverse colleagues and organizations around the world to advance initiatives designed to fill gaps in standards, professional qualifications, and coordination of animal use.
Keywords: Biology and Life Sciences; Agriculture

International Perspectives: The Future of Nonhuman Primate Resources: Proceedings of the Workshop Held April 17-19, 2002 - National Research Council (The National Academies Press, 2003)
The future of nonhuman primate (NHP) resources is a concern of scientists, veterinarians, and funding authorities. An April 2002 workshop brought participants from all over the world to discuss various aspects of the issue such as current shortfalls and excesses in NHP breeding and exportation programs, the status of breeding and conservation programs internationally, the development of specific pathogen-free colonies, difficulties in transporting NHP, and challenges in the management of NHP colonies.
Keywords: Biology and Life Sciences; Agriculture

A Sustainability Challenge: Food Security for All: Report of Two Workshops - National Research Council (The National Academies Press, 2012)
The National Research Council's Science and Technology for Sustainability Program hosted two workshops in 2011 addressing the sustainability challenges associated with food security for all. The first workshop, Measuring Food Insecurity and Assessing the Sustainability of Global Food Systems, explored the availability and quality of commonly used indicators for food security and malnutrition; poverty; and natural resources and agricultural productivity. It was organized around the three broad dimensions of sustainable food security: (1) availability, (2) access, and (3) utilization. The workshop reviewed the existing data to encourage action and identify knowledge gaps. The second workshop, Exploring Sustainable Solutions for Increasing Global Food Supplies, focused specifically on assuring the availability of adequate food supplies. How can food production be increased to meet the needs of a population expected to reach over 9 billion by 2050? Workshop objectives included identifying the major challenges and opportunities associated with achieving sustainable food security and identifying needed policy, science, and governance interventions. Workshop participants discussed long term natural resource constraints, specifically water, land and forests, soils, biodiversity and fisheries. They also examined the role of knowledge, technology, modern production practices, and infrastructure in supporting expanded agricultural production and the significant risks to future productivity posed by climate change. This is a report of two workshops.
Keywords: Agriculture; Environment and Environmental Studies; Food and Nutrition

Atlantic Offshore Renewable Energy Development and Fisheries: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The development of offshore energy on the U.S. Outer Continental Shelf (OCS) is overseen by the Bureau of Ocean Energy Management (BOEM). In support of its mission to conduct its activities in an environmentally and economically responsible way, BOEM engaged a steering committee of the National Academies of Sciences, Engineering, and Medicine to facilitate a workshop about the research and monitoring needed to assess potential impacts from offshore wind turbine installation and operation on fisheries on the Atlantic OCS. This activity is specifically focused on fisheries resources and is one part of a suite of efforts by BOEM to understand the potential impact of offshore renewable energy on the environment. The workshop was focused on southern New England, where several offshore wind leases are progressing toward construction. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences; Energy and Energy Conservation; Agriculture

Data and Research to Improve the U.S. Food Availability System and Estimates of Food Loss: A Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2015)
The United States Department of Agriculture's (USDA's) Economic Research Service's (ERS) Food Availability Data System includes three distinct but related data series on food and nutrient availability for consumption. The data serve as popular proxies for actual consumption at the national level for over 200 commodities (e.g., fresh spinach, beef, and eggs). The core Food Availability (FA) data series provides data on the amount of food available, per capita, for human consumption in the United States with data back to 1909 for many commodities. The Loss-Adjusted Food Availability (LAFA) data series is derived from the FA data series by adjusting for food spoilage, plate waste, and other losses to more closely approximate 4 actual intake. The LAFA data provide daily estimates of the per capita availability amounts adjusted for loss (e.g., in pounds, ounces, grams, and gallons as appropriate), calories, and food pattern equivalents (i.e., "servings") of the five major food groups (fruit, vegetables, grains, meat, and dairy) available for consumption plus the amounts of added sugars and sweeteners and added fats and oils available for consumption. This fiscal year, as part of its initiative to systematically review all of its major data series, ERS decided to review the FADS data system. One of the goals of this review is to advance the knowledge and understanding of the measurement and technical aspects of the data supporting FADS so the data can be maintained and improved. Data and Research to Improve the U.S. Food Availability System and Estimates of Food Loss is the summary of a workshop convened by the Committee on National Statistics of the National Research Council and the Food and Nutrition Board of the Institute of Medicine to advance knowledge and understanding of the measurement and technical aspects of the data supporting the LAFA data series so that these data series and subsequent food availability and food loss estimates can be maintained and improved. The workshop considered such issues as the effects of termination of selected Census Bureau and USDA data series on estimates for affected food groups and commodities; the potential for using other data sources, such as scanner data, to improve estimates of food availability; and possible ways to improve the data on food loss at the farm and retail levels and at restaurants. This report considers knowledge gaps, data sources that may be available or could be generated to fill gaps, what can be learned from other countries and international organizations, ways to ensure consistency of treatment of commodities across series, and the most promising opportunities for new data for the various food availability series.
Keywords: Behavioral and Social Sciences; Food and Nutrition; Agriculture; Surveys and Statistics